PENGARUH PELATIHAN TERHADAP PENINGKATAN PEMAHAMAN PENGELOLA TUBERKULOSIS DI KABUPATEN PAMEKASAN - Rahem, Abdul; Utami, Wahyu; Yuda, Ana; Athiyah, Umi; Priyandani, Yuni; Sulistyarini, Arie; Wijaya, I Nyoman; Hermansyah, Andi; Pristianty, Liza; Sukorini, Anila Impian (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
Tuberculosis (TB) is an infectious disease that ranks second as the cause of death in the infectious disease group after HIV (Human Immunodeficiency Virus) infectious disease. Pamekasan Regency is ranked fifth in East Java in terms of TB cases, after Sumenep, Lumajang, Malang City, and Jember Regencies. The Head of the Pamekasan Regency Health Office is committed to increasing the understanding of TB Cadres to help patients carry out long-term treatment. The activity method was in the form of training on TB Treatment for TB Cadres of Health Centers and TB Managers of the Health Office in Pamekasan Regency. The implementation was held on October 17, 2020 in Pamekasan. There were 58 participants consisting of 35 TB Cadres and 23 TB Managers. The results of the training showed that there was an increase in understanding, with an average score of 8.4828 after the training and 6.6379 before the training with a p pired t test = 0.000. Conclusion The training has an effect on increasing the understanding of TB Cadres and Managers of the Health Office in Pamekasan Regency regarding the treatment and prevention of TB transmission. This activity targets four categories of Sustainable Development Goals (SDGs), namely SDG 3 (Good health and well-being), SDG 4 (Quality education), SDG 16 (Peace, justice and strong institutions) and SDG 17 (Partnership for the goals).